PERILAKU BELANJA ONLINE GENERASI Z DAN DAMPAKNYA TERHADAP INOVASI SISTEM PEMBAYARAN DIGITAL - Wafiq Azizah; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The rapid digital transformation has significantly influenced shifts in consumer behavior, especially among Generation Z, who are recognized as the most active digital and internet users in Indonesia. This study aims to analyze the relationship between Generation Z’s online shopping behavior and the development of digital payment innovations using a library research approach. A total of 25 scientific articles indexed in Google Scholar, OJS Indonesia, and DOAJ published between 2019 and 2024 were reviewed to obtain relevant insights. The findings reveal that Generation Z values speed, convenience, personalization, and security when making online purchases. These expectations have accelerated the adoption of digital payment platforms such as e-wallets, QRIS, and Buy Now Pay Later (BNPL). The increasing reliance on these payment methods does not only facilitate transactions but also supports broader digital financial inclusion across Indonesia. Furthermore, the growing demand from Generation Z encourages financial institutions and fintech companies to continuously innovate, particularly in enhancing cybersecurity features, optimizing service efficiency, reducing transaction fees, and ensuring seamless integration with e-commerce platforms. Generation Z’s online shopping behavior plays a strategic role in shaping the evolution of digital payment systems in Indonesia and will continue to influence future financial technology developments